1978
DOI: 10.1099/00221287-106-1-13
|View full text |Cite
|
Sign up to set email alerts
|

Carboxymethylcellulase Produced by Facultative Bacteria from the Hind-gut of the Termite Reticulitermes hesperus

Abstract: 13Bacillus cereus RWl and Serratia marcescens R W~, isolated from the hind-gut of the termite Reticulitermes hesperus, both grew well on mesquite wood and produced moderate amounts of carboxymethylcellulase. Carboxymethylcellulose (CMC) gels were depolymerized rapidly by 23. cereus Rwl and slowly by S. marcescens RW3. The depolymerization of CMC was pH and temperature sensitive. Depolymerization of gels by growing cultures of B. cereus Rw1 and the action of cell-free extracts of B. cereus Rw1 on CMC sols were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 10 publications
2
25
0
Order By: Relevance
“…Several studies have shown that B. subtilis can be used as a host to secrete heterologous cellulases, and naturally occurring strains have been identified that secrete cellulases (26,27,53,57,62,63). Cellulase enzymes have also been targeted to the membrane, enabling protoplasts of B. subtilis to degrade CMC (29).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that B. subtilis can be used as a host to secrete heterologous cellulases, and naturally occurring strains have been identified that secrete cellulases (26,27,53,57,62,63). Cellulase enzymes have also been targeted to the membrane, enabling protoplasts of B. subtilis to degrade CMC (29).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the appearance of rare or nonnative bacterial members in the rifampin-treated guts may be affected by interactions with other bacteria. For example, the Serratia marcescens 16S rRNA gene sequence identified in our study is 99.9% identical to that of an opportunistic pathogen of termites that has been hypothesized to induce replication of normal termite gut bacteria by suppressing the host immunity, changing available oxygen, and producing bacterial growth-promoting enzymes such as carboxymethyl cellulase (1,19,68,75). A Serratia-induced proliferation of the symbiotic community could cause septicemia, which can result in early termite mortality (75).…”
Section: Discussionmentioning
confidence: 98%
“…As cellulolytic enzyme systems of other organisms are generally repressed by glucose (12,30,53,55), the effect observed here is quite unusual. Thayer (58) has also reported increased ,B-1,4-glucanase activity by B. cereus in the presence of glucose. It remains to be determined whether glucose itself acts as an inducer of enzyme synthesis or whether the stimulatory effect on P-1,4-glucanase production by glucose is more indirect.…”
mentioning
confidence: 99%